Behavior of GFRP strengthening masonry walls using glass fiber composite anchors. (February 2021) - Abdulsalam, Bahira; Ali, Ahmed H.; ElSafty, Adel; Elshafey, Nasser
Abstract: This paper presents experimental and theoretical investigations on the short-term behavior of stone masonry walls constructed with lime mortar. The walls were strengthened using unidirectional GFRP (Glass fiber reinforced polymers) sheets to resist out-of-plane loads. Two methods of anchorage were used to enhance the behavior of strengthened stone masonry walls by preventing premature peeling-off of the GFRP sheets caused by GFRP debonding. Nine GFRP strengthened limestone masonry wall specimens including two control specimens were tested under combined constant low axial load levels and out-of-plane bending caused by two point monotonic loading. All the specimens have height-to-thickness ( h / t ) ratio of 7.1. The main variables investigated were GFRP reinforcement ratio, arrangement of GFRP, axial load level, and anchorage method. The strengthened walls showed an improvement in the out-of-plane performance which was significantly enhanced by anchorage. The increase in wall ultimate load carrying capacity reached 100%.